Autonomous, bidding, credible, decentralized, ethical, and funded (ABCDEF) publishing [version 2; peer review: 1 approved, 2 approved with reservations] - Kyoshiro Sasaki; Kohei Ueda; Masahito Yamagata; Yuki Mori; Hiro Taiyo Hamada; Taiki Oka; Kaito Takashima; Yuki Yamada (F1000Research, 2023)
Scientists write research articles, process ethics reviews, evaluate proposals and research, and seek funding. Several strategies have been proposed to optimize these operations and to decentralize access to research resources and opportunities. For instance, we previously proposed the trinity review method, combining registered reports with financing and research ethics assessments. However, previously proposed systems have a number of shortcomings, including how to implement them, e.g., who manages them, how incentives for reviewers are paid, etc. Various solutions have been proposed to address these issues, employing methods based on blockchain technologies, called “decentralized science (DeSci)”. Decentralized approaches that exploit these developments offer potentially profound improvements to the troubled scientific ecosystem. Here, we propose a system that integrates ethics reviews, peer reviews, and funding in a decentralized manner, based on Web3 technology. This new method, named ABCDEF publishing, would enhance the speed, fairness, and transparency of scientific research and publishing.